How Implicatures Create Funnines In Comic Strips ? - Saffanah, Aurell Videla; Putri, Amelia Herdia; Al Farisi, Fakhri; Jaufilaili, Jaufilaili; Mulatsih, Devi (Devotion : Journal of Research and Community Service, 2024)
This research is aimed to analyze types of flouting maxim. To find cooperative principle of the implicature through the utterances expressed from the characters in comic strips. The method that will be used in this research is qualitative research design. The researchers use 12 chapters of the tiger comic strips from comics kingdom website as data source from December 01, 2023 to January 24, 2024. Then analyze the conversation that the character had. Likewise, this study attempts to discover the reason for using implicature in the comic strips. The researchers draw a conclusion where the flouting maxim of quantity (32.5%), the flouting maxim of quality (20%), the flouting maxim of manners (25%), and the flouting maxim of relevant (22.5%). The characters of “Tiger” digital comic strips mostly flouted the maxim of quantity since they avoid making others upset about lack of the answer, so they provide a comprehensive explanation.